2007
DOI: 10.1158/1078-0432.ccr-07-1113
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of KIAA0101 Predicts High Stage, Early Tumor Recurrence, and Poor Prognosis of Hepatocellular Carcinoma

Abstract: KIAA0101 correlates with enhanced metastatic potential and is a significant prognostic factor of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(111 citation statements)
references
References 43 publications
9
102
0
Order By: Relevance
“…KIAA0101 overexpression was associated with concomitant p53 mutation and vascular invasion (Yuan et al, 2007). This study suggested that high expression in hepatocellular carcinoma was indicative of tumour recurrence, metastatic potential and poor prognosis (Yuan et al, 2007).…”
Section: Hepatocellular Carcinomamentioning
confidence: 76%
See 3 more Smart Citations
“…KIAA0101 overexpression was associated with concomitant p53 mutation and vascular invasion (Yuan et al, 2007). This study suggested that high expression in hepatocellular carcinoma was indicative of tumour recurrence, metastatic potential and poor prognosis (Yuan et al, 2007).…”
Section: Hepatocellular Carcinomamentioning
confidence: 76%
“…Not detected in heart or liver (Yu et al, 2001). The KIAA0101 protein was down-regulated in human hepatocellular carcinoma (Guo et al, 2006;Yuan et al, 2007). Increased protein levels have been detected in pancreatic cancer cells (Hosokawa et al, 2007).…”
Section: Expressionmentioning
confidence: 97%
See 2 more Smart Citations
“…The protein product of the KIAA0101/p15 PAF gene is a protein implicated in proliferation and proliferating cell nuclear antigen (PCNA)-mediated DNA repair, all the while displaying oncogenic activity when aberrantly expressed, possibly through the same aforementioned pathway (89). Overexpression of KIAA0101 has been linked to growth and invasiveness of adrenal cancer (38), a predictor of poor survival in primary lung cancer (86), breast cancer (35), hepatocellular carcinoma (106), and gastric cancer (111). Although no published studies exist on KIAA0101 expression in MPM to date, based on the above it is likely that its previously mentioned PCNA-mediated oncogenic properties may play a major part.…”
Section: Functional Enrichment Annotation Analysis Of Gene Ontologiesmentioning
confidence: 99%